2008
DOI: 10.7589/0090-3558-44.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Columbid Herpesvirus-1 in Two Cooper's Hawks (Accipiter Cooperii) With Fatal Inclusion Body Disease

Abstract: ABSTRACT:We report two separate naturally occurring cases of fatal herpesviral disease in Cooper's Hawks (Accipiter cooperii). Gross lesions included splenomegaly and hepatomegaly, with diffuse pale mottling or scattered small white foci. Histologic lesions included splenic and hepatic necrosis associated with eosinophilic intranuclear inclusion bodies characteristic of herpesvirus. In one case, necrosis and inclusions were also noted in bone marrow, thymus, bursa of Fabricius, thyroid gland, parathyroid gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…The results obtained in our study confirm previous findings that all recently reported herpesviruses from birds of prey belong to CoHV-1 [1,5,13,14,27]. Indeed, herpesviruses are not restricted to a specific host or tissue and may cross the barriers of the specific host.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results obtained in our study confirm previous findings that all recently reported herpesviruses from birds of prey belong to CoHV-1 [1,5,13,14,27]. Indeed, herpesviruses are not restricted to a specific host or tissue and may cross the barriers of the specific host.…”
Section: Discussionsupporting
confidence: 91%
“…[3] as an agent affecting pigeons that caused visceral lesion such as necrosis especially in liver. Herpesvirus infection was frequently identified in young pigeons and free-ranging birds from different countries of Europe [12,16,20-22], Iraq [23], USA [1,13,15], Australia [4,14] and Canada [5]. The virus is antigenically related to CoHV-1 and was found in falcons and owls [1,4,5,12-16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations